DMTA analysis for long-term mechanical behaviour prediction of PMMA-based bone cements - Guedes, RM (2006)
Poly(methyl methaerylate) (PMMA) is commonly used as acrylic bone cement to fix bone implants. In vivo degradation of bone cement may lead to a decrease in mechanical properties and result in aseptic loosening. Creeping can promote failure of the implant. This study used dynamic mechanical thermal analysis (DMTA) equipment, in the 0.01 to 50 Hz frequency range, to investigate the dynamic viscoelastic relaxation characteristics of CMW (TM), PROFIT QUIRURGICO and PALACOS PMMA-based bone cements. Their initial moduli were measured as 2450, 1850 and 1710 MPa, respectively. Relaxation master curves displayed similar features. The DMTA temperature range was between 20 and 75 degrees C. Predictions for long-term relaxation moduli were analyzed and compared against published experimental data. The comparison revealed that master curves obtain using the time-temperature-superposition principle (TTSP) present a much slower relaxation modulus compared to long-term experimental data above 1000 s. However, extrapolations based on a time-power law applied to isothermal experimental data allow better long-term predictions.